Moderating Effect of Demographic Profile on Employee Engagement and Productivity - Belostrino, Maria Regina; Estiller, Renalyn (Journal of Interdisciplinary Perspectives, 2024)
This study explores the moderating effect of demographic profile on employee engagement and productivity in Cavite, Philippines. The study focused on the 321 service crews working in the Quick Service Restaurants (QSRs), who were selected through a simple random technique. The findings show that productivity is negatively impacted by physical engagement. This suggests an effect between more customer complaints and less physical engagement. Accuracy and quality are affected by emotional engagement, indicating that a drop in emotional engagement could result in a drop in quality. Other types of engagement, such as trait, behavioral, psychological, and cognitive, do not affect productivity. The results are consistent with earlier studies, emphasizing the role that engagement dimensions, including physical, emotional, cognitive, trait, psychological state, and behavioral, play in raising productivity in the service industry. The study also emphasizes how important demographic characteristics are in determining how engagement and productivity are related. Gender does not significantly attenuate this association; nevertheless, other demographic factors that are important to consider are age, marital status, duration of service, and monthly wage. Theoretical implications imply that, in contrast to conventional wisdom, gender may not significantly impact employee productivity in QSRs. In practical terms, the non-significant gender moderation effect highlights how crucial it is to implement gender-neutral engagement tactics to raise worker productivity and levels of engagement. The study suggests future paths for research and offers useful implications for organizational management.